Tindak Pidana Prostitusi Online dalam Perspektif Hukum Positif dan Hukum Islam - Saleh, Triana Galuh Purnama Sari; Nurussaadah, Ilusya; Putri, Ila Adila pramestya (Al-Jinayah : Jurnal Hukum Pidana Islam, 2022)
Abstract: The extent of the reach of the internet that can be accessed, it is not uncommon for people to take advantage of this to carry out negative actions, one of which is online prostitution. This paper is based on the rampant prostitution activities in cyberspace lately. The existence of covid and the implementation of activity restrictions can be the cause of some people being laid off from their jobs so they want to make money in an easy and instant way. Prostitution is a negative thing, therefore there are regulations regarding prostitution both in positive law and Islamic law. This research method uses a qualitative approach by reviewing previous research so that data can be reprocessed for deeper understanding. Based on the results of the study, it can be concluded that, in positive law and Islamic law there are discussions about online prostitution, and there are sanctions against perpetrators of prostitution activities. Positive law has been regulated in several articles of the law, one of which is Law Number 11 of 2008 concerning Electronic Information and Transactions which regulates the prohibition of distributing and/or transmitting and/or making accessible Electronic Information and/or Electronic Documents containing which violates decency. In addition, Islamic law also regulates the punishment for online prostitution as stated in the Al-Quran Surah An-Nur verse 2 which contains provisions regarding the prohibition of adultery and the sanction is a punishment of 100 lashes of lashes. Keywords: Online Prostitution, Positive Law, Islamic Law